Implementasi Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (Pamsimas) di Desa Kebon Kecamatan Paron Kabupaten Ngawi: Studi di Desa Kebon, Kecamatan Paron, Kabupaten Ngawi - Ayu Nindya, Arwinda Arum; Subaris Kasjono, Heru; Sugianto, Sugianto; Rois , Ibnu (Poltekkes Kemenkes Bengkulu, 2025)
Background: Indonesia is the fourth most populous country in the world, yet access to clean water remains unevenly distributed. This situation is a critical issue as it affects various aspects of life, including public health and community well-being. The Community-Based Drinking Water and Sanitation Program (PAMSIMAS) is one of the central government's efforts to improve access to clean water and sanitation in rural areas through a community empowerment approach. The PAMSIMAS program in Kebon Village has been running since 2019, covering 330 household connections and facilitated by the Regional Development Planning Agency (BAPPEDA).Methods: A qualitative method was used, with the results presented in the form of frequency distribution tables. Results: The study showed that the program’s success level was categorized as very good in all aspects, although some issues were noted, including limited water quantity, handwashing with soap practices (HWWS), program implementation challenges, and limited operational funding. Conclusion: The implementation of the PAMSIMAS program in Kebon Village is considered very good but still requires improvements in technical aspects and budgetary support. Keywords: PAMSIMAS, Clean Water, Sanitation, Healthy and Hygienic Behavior